PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SDN 5 KARANG ANYAR LAMPUNG SELATAN - Tri Maya Sari; Dwi Wulandari; Yeni Susilawati (Al Mufid, 2023)
This study aims to determine and analyze the increase in learning outcomes of fifth grade students at SDN 5 Karang Anyar Jati Agung South Lampung through discovery learning models. The problem of this research is the low interest in learning and the interest of students in the learning process so that it affects the low learning outcomes of students. The research subjects were fifth grade students of Odd Semester SD Negeri 5 Karang Anyar South Lampung which consisted of 24 students, while the objects in the study were learning outcomes. The implementation method uses two stages, namely: the preparation stage and the implementation stage. The results of the study show that using discovery learning models can improve the learning outcomes of fifth grade students at SDN 5 Karang Anyar Jati Agung South Lampung.